Circulating membrane aminophospholipids contribute to thrombotic risk in rheumatoid arthritis - Daniela O. Costa; Majd B. Protty; Victoria J. Tyrrell; Ali A. Hajeyah; Bethan H. Morgan; Ben Mead; Martin Giera; Peter W. Collins; P. Vince Jenkins; Ernest Choy; Simon A. Jones; Valerie B. O’Donnell (Journal of Lipid Research)
Patients with rheumatoid arthritis (RA) are at elevated risk of thrombotic events, yet the underlying mechanisms remain unknown. The contribution of the procoagulant membrane surface provided by aminophospholipids (aPLs) in driving thrombotic risk in RA has not been investigated. Specifically, neither the type of aPL exposed on circulating blood cell membranes in patients is characterized nor is their ability to support thrombin generation is known. Here, lipidomics was used to characterize the external-facing and total levels of aPL molecular species in RA, specifically phosphatidylserine and phosphatidylethanolamine on extracellular vesicles (EVs), platelets, and white blood cells (WBCs). The ability of the cells and EVs to support thrombin generation from patients and healthy controls was compared using an in vitro prothrombinase assay. RA patient plasma had significantly higher levels of thrombin-antithrombin and d-dimers, indicating increased thrombotic activity in vivo. Higher EV and platelet counts were seen in RA, but WBC counts were not elevated. EVs from RA patients supported higher levels of thrombin generation compared with healthy controls, whereas for platelets and WBC, thrombin generation was similar for both groups. EVs from RA patients also showed elevated external-facing phosphatidylserine molecular species, with total aPL also increased. For platelets and WBC, total and external-facing aPL levels were similar. Thrombin-antithrombin (TAT) complexes significantly correlated with EV particle counts, indicating that their circulating numbers are directly related to coagulation in vivo. Overall, our data suggest that elevated plasma EV levels in RA are a major source of procoagulant membranes, contributing to thrombotic risk in RA.